The data science workshop a new, interactive approach to learning data science - So, Anthony (Packt, 2020)
bCut through the noise and get real results with a step-by-step approach to data science/b h4Key Features/h4 ulliIdeal for the data science beginner who is getting started for the first time /li liA data science tutorial with step-by-step exercises and activities that help build key skills /li liStructured to let you progress at your own pace, on your own terms /li liUse your physical print copy to redeem free access to the online interactive edition/li/ul h4Book Description/h4 You already know you want to learn data science, and a smarter way to learn data science is to learn by doing. The Data Science Workshop focuses on building up your practical skills so that you can understand how to develop simple machine learning models in Python or even build an advanced model for detecting potential bank frauds with effective modern data science. You'll learn from real examples that lead to real results.